ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN TERHADAP KUALITAS BAKTERIOLOGIS PADA AIR SARANA PAMSIMAS DI KECAMATAN LAMPIHONG KABUPATEN BALANGAN - Wijaya, Herman; Fatmawati, Fatmawati; Rahman, Mijani; Suhartono, Eko (EnviroScienteae, 2024)
Clean water is a very vital need for all humans. The PAMSIMAS Program is a community-based drinking water and sanitation provision activity carried out on the basis of cooperation between the Central Government, Regional Government and the World Bank. Balangan Regency has approximately 56 units of PAMSIMAS facilities, especially in Lampihong District. Water at PAMSIMAS facilities with raw water sources using drilled wells will experience a decline in bacteriological quality in 2022 (does not meet quality standards). So this research aims to analyze the bacteriological quality of Sarana PAMSIMAS water and analyze factors related to the bacteriological quality of Sarana PAMSIMAS water in Lampihong District, Balangan Regency. This research was carried out in Lampihong District, Balangan Regency from October to December 2023. The research was carried out by analyzing bacteriological quality and directly observing risk factors related to bacteriological quality. The data analysis used in this research is logistic regression analysis using the backward method. The results of the bacteriological quality analysis show that in measuring the Total coliform in the morning samples there was 1 sample in Matang Lurus Village RT.02 which met the quality standards while at other locations the Total coliform content was higher. of 0, while in the samples taken in the afternoon there were 5 (five) samples that met the quality standards while the other 5 (samples) contained Total coliforms of more than 0. The results of measuring Escherichia coli in the morning samples contained 2 observation points that contained The Escherichia coli is equal to 0, while in the samples taken in the afternoon there were 3 samples containing Escherichia coli more than 0. Meanwhile, based on the results of logistic regression analysis using the backward method, it can be seen that factors that either partially or simultaneously influence Bacteriological quality of water at PAMSIMAS facilities that use drilled wells as a source of raw water, namely Pegurasan reservoir and water treatment.